Immune responses induced by oligogalacturonides are differentially affected by AvrPto and loss of BAK1/BKK1 and PEPR1/PEPR2. (26th July 2016) - Gravino, Matteo; Locci, Federica; Tundo, Silvio; Cervone, Felice; Savatin, Daniel Valentin; De Lorenzo, Giulia
Summary: Plants possess an innate immune system capable of restricting invasion by most potential pathogens. At the cell surface, the recognition of microbe‐associated molecular patterns (MAMPs) and/or damage‐associated molecular patterns (DAMPs) by pattern recognition receptors (PRRs) represents the first event for the prompt mounting of an effective immune response. Pathogens have evolved effectors that block MAMP‐triggered immunity. The Pseudomonas syringae effector AvrPto abolishes immunity triggered by the peptide MAMPs flg22 and elf18, derived from the bacterial flagellin and elongation factor Tu, respectively, by inhibiting the kinase function of the corresponding receptors FLS2 and EFR, as well as their co‐receptors BAK1 and BKK1. Oligogalacturonides (OGs), a well‐known class of DAMPs, are oligomers of α‐1, 4‐linked galacturonosyl residues, released on partial degradation of the plant cell wall homogalacturonan. We show here that AvrPto affects only a subset of the OG‐triggered immune responses and that, among these responses, only a subset is affected by the concomitant loss of BAK1 and BKK1. However, the antagonistic effect on auxin‐related responses is not affected by either AvrPto or the loss of BAK1/BKK1. These observations reveal an unprecedented complexity among the MAMP/DAMP response cascades. We also show that the signalling system mediated by Peps, another class of DAMPs, and their receptors PEPRs, contributes to OG‐activated immunity. We hypothesize that OGs are sensed through multiple and partially redundant perception/transduction complexes, some targeted by AvrPto, but not necessarily comprising BAK1 and BKK1.